First description of the female of Psalistopoides fulvimanus Mello-Leitão, 1934 (Araneae: Pycnothelidae) - Brescovit, Antonio D.; Lucas, Sylvia M.; Marques-Da-Silva, Emanuel; Sherwood, Danniella; Silvério, Heloisa F. [UNESP] (Arachology, 2023)
The unknown female of Psalistopoides fulvimanusMello-Leitão, 1934 is described for the first time. Specimens from the state of Paraná were examined and new records were from additional localities were made, expanding its known distribution in Brazil.
Keywords: biogeography; morphology; Mygalomorphae; spermathecae; taxonomy